2012
DOI: 10.1111/j.1748-5827.2012.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of a water‐soluble micellar paclitaxel (Paccal Vet) in canine mastocytomas

Abstract: Objective To determine the clinical efficacy and safety of a cremophor‐free formulation of paclitaxel (Paccal Vet, Oasmia Pharmaceuticals) in dogs with mast cell tumours. Methods Paccal Vet was administered at a median dose of 145 (range, 135 to 150) mg/m2intravenously once every 21 days for three cycles to 29 dogs with macroscopic grade 2 or 3 mast cell tumour. Efficacy was assessed by tumour response (Response Evaluation Criteria in Solid Tumours version 1.0) and performance status score. Progression‐free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…itching, flushing, palpitations, cardiovascular collapse) [103]. A recent study evaluated the clinical safety and efficacy of a cremophor-free formulation of paclitaxel (Paccal Vet, Oasmia Pharmaceuticals) in dogs with MCTs [104]. Paclitaxel acts blocking the mitotic spindle, with cell-cycle arrest and subsequent apoptosis of tumor cells.…”
Section: Treatment Of Human Mastocytosis and Cmctsmentioning
confidence: 98%
See 1 more Smart Citation
“…itching, flushing, palpitations, cardiovascular collapse) [103]. A recent study evaluated the clinical safety and efficacy of a cremophor-free formulation of paclitaxel (Paccal Vet, Oasmia Pharmaceuticals) in dogs with MCTs [104]. Paclitaxel acts blocking the mitotic spindle, with cell-cycle arrest and subsequent apoptosis of tumor cells.…”
Section: Treatment Of Human Mastocytosis and Cmctsmentioning
confidence: 98%
“…Paclitaxel acts blocking the mitotic spindle, with cell-cycle arrest and subsequent apoptosis of tumor cells. Furthermore, itmay display anti-angiogenic properties targeting endothelial cells and, given its low specificity, it is indicated for both c-kit mutated and wild-type MCTs treatment, compared to the targeted MCTs therapies [104]. The new formulation of paclitaxel (Paccal Vet) consists of a water-soluble drug, since the molecule is formulated in nanoparticles.…”
Section: Treatment Of Human Mastocytosis and Cmctsmentioning
confidence: 99%
“…Results from this phase I/II study of Paccal Vet ® led to a multi‐center European, open label, single‐arm study of Paccal Vet ® to determine the efficacy and safety in dogs with grade II or III mast cell tumors . The study resulted in the accrual of 29 dogs with mast cell tumors.…”
Section: Clinical Development Of Paccal Vet® For Dogs With Cancermentioning
confidence: 99%
“…As such, further discussion in this manuscript of Paccal ® 's use on cancers, whether published or not, that do not fall under this conditionally approved label has been limited. We nonetheless recognize the reasonable interest of the oncology community in these published studies, that include early phase studies in several cancer types, and more prominent later phase randomized studies in dogs with mast cell tumors. Briefly, the activity of Paccal ® in dogs with a variety of measurable cancers in early phase studies was demonstrated and may be considered to be reasonable evidence of its expected activity in a variety of canine cancers in dogs .…”
Section: Clinical Development Of Paccal Vet® For Dogs With Cancermentioning
confidence: 99%
“…, Rivera et al . ). The inclusion of questions regarding PA confirms the importance of its evaluation in QOL assessment but using this methodology, it is difficult to quantify changes in PA and the results may be biased by client preconceptions of chemotherapy.…”
Section: Introductionmentioning
confidence: 97%